Fundamental aspects of processing multi-metallic components using additive manufacturing technologies - Amin S. Azar; Spyros Diplas (European Journal of Materials, 2022)
Additive Manufacturing (AM) has triggered development of advanced materials and supply chain strategies. Almost all newly launched metallurgical processing routes had initial technical limitations arising from the fact that their process-property-performance relationship is not well-explored. In the same context, understanding the ramifications of the transition from “conventional” to “additive” manufacturing, requires knowledge of the physical mechanisms associated with technical challenges. The latter becomes bolder when processing of multi-metallic components is addressed. The first half of the article is devoted to the status and recent progress in AM processing practices. We emphasize on the role of processing parameters and instrumentation-material interaction in various AM methods with focus on multi-metallic materials. The second half addresses material development and performance perspectives with emphasis on multi-metallic configurations. Crucial factors for structural integrity are introduced and specific technical challenges are demonstrated, considering engineering materials for multi-metallic components. It is also demonstrated how various cooling rates measurement techniques can be utilised for assessing the cooling rates in AM. Post processing challenges associated with the corrosion performance of bimetallic components and the effect of heat treatment on AM components are also included. Finally, the role, origin and detection of residual stresses in AM components are addressed.